The bright side of procedures in a period of crisis: acquisitions decision-making at the EUI Library - Alpigiano, Carlotta; Daalder, Martine (Qualitative and Quantitative Methods in Libraries; Vol 4 No 3 (2015): September 2015 Issue, 2017)
As demand for new resources increases and purchasing powers diminish, libraries are obliged to apply selection and revision criteria in their collection development policy. The European University Institute, an international research institution for post-graduate studies on social sciences, has developed a firm workflow from the initial proposal of a new resource to annual renewal / cancellation /switch from print to online. Decisions are made considering specific criteria, including costs, usage statistics, academic feedback, technical specifications, preservation availability, alternative ways of providing information required. The EUI Library‟s technical environment includes: ILS Millennium with ERM module integrated with Primo Discovery tool, statistics software managing a collection of data and P.I. according to the Sconul scheme and SAP accounting system.